Identifying Organizational Factors and Components Influencing Customer Experience Management Maturity: A Meta-synthesis Approach - Payam Mardazad Navi; Kambiz Heidarzadeh Hanzaee; Seyyed Buik Mohammadi; Mohsen Khoon Siavash (‫مدیریت بازرگانی)
Objective Since the mid-1950s, many subjects related to customer experience, including measuring the customer experience, its effect on loyalty and brand, etc. have been studied because building a strong customer experience is currently one of the most important management goals. The explosion of potential touch points and diminishing control over the customer experience requires companies to integrate multiple business functions such as IT, service operations, logistics, marketing, human resources, external partners, and supply chains to create and deliver a positive customer experience. The purpose of this study is to systematically review organizational factors and components effective on customer experience management using the meta-synthesis method.